Implementasi Media Pembelajaran Ular Tangga Numerasi dalam Program Kampus Mengajar 7 di SDN 35 Ampenan - Mawarni, Ririn; Anugrah, Inayah; Anjani, Tik Kun; Renata, Zabina; Sorayya, Hilalatus; Wulandari, Nourma Pramestie (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Kampus Mengajar was one of MBKM's programs established to help improve learning in schools. The targets of the Kampus Mengajar program were schools located in 3T areas or schools with poor numeracy and literacy levels. One of the schools targeted by Kampus Mengajar and used as a place of service was SDN 35 Ampenan. SDN 35 Ampenan was one of the schools in the Sekarbela sub-district, Mataram City, which, in terms of the level of students' numeracy and literacy, was below standard. The way to improve numeracy and literacy in schools was to use fun learning media. Educational material in the form of a snakes and ladders game was one of the approaches used. This game was conducted to improve students' knowledge in numeracy and literacy, teach students cohesiveness in teamwork, and reinforce students' memory of previously taught lessons. The work program of this learning media using the Snakes and Ladders game can enhance understanding and student engagement in the learning process. It makes students more enthusiastic about participating in lessons and helps prevent boredom with the classroom environment. Based on the results of this work program, students have been able to solve problems that exist in the school.